A Trk/HKT-Type K(+) Transporter from Trypanosoma brucei - Mosimann, Marc (American Society for Microbiology, 2010)

(untitled)
The molecular mechanisms of K(+) homeostasis are only poorly understood for protozoan parasites. Trypanosoma brucei subsp. parasites, the causative agents of human sleeping sickness and nagana, are strictly extracellular and need to actively concentrate K(+) from their hosts’ body fluids. The T. brucei genome contains two putative K(+) channel genes, yet the trypanosomes are insensitive to K(+) antagonists and K(+) channel-blocking agents, and they do not spontaneously depolarize in response to high extracellular K(+) concentrations. However, the trypanosomes are extremely sensitive to K(+) ionophores such as valinomycin. Surprisingly, T. brucei possesses a member of the Trk/HKT superfamily of monovalent cation permeases which so far had only been known from bacteria, archaea, fungi, and plants. The protein was named TbHKT1 and functions as a Na(+)-independent K(+) transporter when expressed in Escherichia coli, Saccharomyces cerevisiae, or Xenopus laevis oocytes. In trypanosomes, TbHKT1 is expressed in both the mammalian bloodstream stage and the Tsetse fly midgut stage; however, RNA interference (RNAi)-mediated silencing of TbHKT1 expression did not produce a growth phenotype in either stage. The presence of HKT genes in trypanosomatids adds a further piece to the enigmatic phylogeny of the Trk/HKT superfamily of K(+) transporters. Parsimonial analysis suggests that the transporters were present in the first eukaryotes but subsequently lost in several of the major eukaryotic lineages, in at least four independent events.